Effects of habitual water exercise on heart rate, oxygen uptake, rectal temperature and thermal sensation scale - Komiyama, M.; Nishimura, K.; Onodera, S. (Japanese Journal of Sciences in Swimming and Water Exercise, 2006)
The purpose of this study was to investigate the effects of habitual water exercise on heart rate, oxygen uptake, rectal temperature and thermal sensation scale. Thirty healthy males volunteered to participate in this study. Subjects were divided into the habitual water exercise group (WE-group) and the control group (C-group). After resting in a supine position on a land, subjects were moved into water and performed a supine floating for 20 minutes. After the immersion, they were moved to a land and rested for 10 minutes in a sitting position for a recovery. Water temperature was 30 degrees Celsius. Heart rate, oxygen uptake, rectal temperature, blood pressure and thermal sensation scale were measured. Oxygen uptake was significantly low (p< 0.05) in WE-group in comparison of the C-group during a recovery. Thermal sensation scale of WE-group was significantly lower (p< 0.05) than that of the C-group during a supine floating. These results suggest that the habitual water exercise significantly influenced oxygen uptake and thermal sensation scale.